Abstract: The article analyzes the subjective rights of minor family members, notes the lack of unambiguous views among scholars on the content of subjective rights, which gives this issue special relevance. The author formulates a group of subjective rights that have different content and content, and also comes to the conclusion that it is necessary to distinguish between subjective public and private rights of minor family members. - Samoilov T. V., Petrov D. S. (Socio-Cultural and Psychological Problems of the Modern Family: Current Issues of Assistance and Support, 2023)
Abstract: The article analyzes the subjective rights of minor family members, notes the lack of unambiguous views among scholars on the content of subjective rights, which gives this issue special relevance. The author formulates a group of subjective rights that have different content and content, and also comes to the conclusion that it is necessary to distinguish between subjective public and private rights of minor family members.
Keywords: общество; семья; society; family; закон; несовершеннолетний; law; minor; subjective; субъективные права